Occupational Ergonomics and Safety, Part 2 - Arezes, P. (2015)
[Excerpt] This section is the second part of a special issue on Occupational Ergonomics and Safety, which was organized for WORK: A Journal of Prevention, Assessment and Rehabilitation. As in the first part of this thematic issue, this one comprises thirteen papers that were peer-reviewed and, finally, accepted for publication. This issue includes the work of authors from eleven countries all over the world. The variety of the presented works is not limited to their geographical origin, but it is also visible on the topics that are addressed, ranging from typical studies on ergonomics to safety management studies, as well as occupational hygiene topics.